Are maternal symptoms of depression/PTSD and Child Genetic risk scores for depression/PTSD associated with childhood subcortical brain volumes? - Grobler, Anje-Lore (Department of Psychiatry and Mental Health, 2025)
The antenatal period is a critical window for genetic and environmental factors to influence a child's brain development. While previous research in East Asian and European populations has linked child polygenic risk scores (PRSs) for depression and maternal antenatal symptoms (E) to child subcortical brain volumes, these associations remain unexplored in African populations. Moreover, PRSs for post-traumatic stress disorder (PTSD) have not been investigated in relation to child subcortical brain volumes. This study examined: 1) the effects of child genetic risk for depression and PTSD (G), including the interaction with maternal antenatal symptoms of depression and PTSD (G+E or GxE), on child subcortical brain volumes at two years of age; and 2) the genetic architecture of these brain volumes. Using PRS-CSx, PRSs were derived from Psychiatric Genomics Consortium summary statistics, with the Drakenstein Child Health Study (N = 128) as the target dataset. Associations between child genetic risk, maternal antenatal symptoms and child subcortical brain volumes were tested using linear regression. A genome-wide association study (GWAS; N = 163) was used to investigate genetic associations with these subcortical volumes, and trans-ancestry genetic correlations between African and European cohorts were estimated using Popcorn. For depression, model G was associated with larger total thalamus, left thalamus, and left hippocampus volumes, and smaller right thalamus, bilateral putamen and total pallidum volumes. Model GxE was associated with larger bilateral caudate volume. For PTSD, model G was associated with larger total and right putamen and right pallidum volume, and with smaller left putamen and left hippocampus volume. Model G+E was associated with larger total thalamus and right thalamus volumes, and model GxE with larger bilateral caudate volumes. No SNPs reached genome-wide significance, but three SNPs showed trending associations: rs6052713 (left caudate), rs11771415, and rs7317597 (right hippocampus). No significant cross-population genetic correlations were identified. This study provides preliminary evidence of gene-environment interactions influencing child subcortical brain volumes in a South African population. Findings partially align with prior research and highlight the need for larger studies to clarify the mechanisms linking maternal mental health, child genetics, and brain development.